Nike and the balancing act between social justice and selling products - Murfree, Jessica R.; Burpo, Brigitte M.; Hambrick, Marion E. (London : SAGE Publications: SAGE Business Cases Originals, 2020)
In 2018, Nike faced a challenging decision: balancing its support for product endorser Colin Kaepernick while maintaining a longstanding relationship with its industry partner, the National Football League (NFL). In 2016, Kaepernick, then a San Francisco 49ers quarterback, ignited a national protest against police brutality by sitting while the national anthem was played before an NFL preseason game. His attempt to raise awareness about racial oppression in the United States prompted support and opposition for the player, his team, and the league. Two years after the initial protest, Nike produced a controversial "Just Do It" commercial celebrating its 30th anniversary and used Kaepernick as the face of the campaign. This case study asks readers to assess Nike's efforts to support athlete activism while simultaneously managing relations with potential opponents of these efforts and generating revenues.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Kaepernick, Colin, -- 1987-; Nike (Firm); San Francisco 49ers (Football team); Social responsibility of business -- United States -- Case studies; Political activists -- United States -- Case studies